1986
DOI: 10.1021/bi00367a037
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of phosphoenolpyruvate carboxylation catalyzed by phosphoenolpyruvate carboxykinase

Abstract: The stereochemistry of the carboxylation of phosphoenolpyruvate to yield oxalacetate, catalyzed by chicken liver phosphoenolpyruvate carboxykinase and by Ascaris muscle phosphoenolpyruvate carboxykinase, was determined. The substrate (Z)-3-fluorophosphoenolpyruvate was used for the stereochemical analysis. The carboxylation reaction was coupled to malate dehydrogenase to yield 3-fluoromalate, and the stereochemistry of the products was identified by 19F NMR. In separate experiments, the enantiomeric tautomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…The ultimate products were identified as 3-fluorolactate, (2R,3R)-3-fluoromalate, and (2R,3S)-3-fluoromalate by comparison to authentic samples (Figure 1). The assignments are consistent with those of Keck et al (1980) and Hwang and Nowak (1986).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The ultimate products were identified as 3-fluorolactate, (2R,3R)-3-fluoromalate, and (2R,3S)-3-fluoromalate by comparison to authentic samples (Figure 1). The assignments are consistent with those of Keck et al (1980) and Hwang and Nowak (1986).…”
Section: Resultssupporting
confidence: 91%
“…In addition, the ratio of (2R,3R)-3-fluoromalate to (2R,3S)-3-fluoromalate was constant, indicating that reduction of F-OAA was rapid relative to racemization. Goldstein et al (1978) and Hwang and Nowak (1986) reported that racemic 3-fluorooxalacetate was converted by MDH to a mixture of (2R,3R)-3-fluoromalate and (2R,3S)-3-fluoromalate without significant stereoselectivity." While (a-F-PEP is only carboxylated 3% of the time, (Z)-Cl-PEP is reported to undergo 25% carboxylation and 75% hydrolysis (Liu et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…8A) and that their active site cysteines act as the acid/base catalyst. The occurrence of neutral residues for the second group of enzymes agrees with their documented 2-si-stereoreactivity: PK (63,64), PEPC (65), DAHPS (66), EPSPS (67), MurA (68), and PEPCK (69). The potential catalytic residues of these enzymes were localized in these superimposed structures by comparison with the Cys-115 of MurA (Fig.…”
Section: Cys-502 Counterparts In Homologous Ei and Insupporting
confidence: 73%
“…Most of the pseudosubstrates or competitive inhibitors discovered so far differed from PEP by the presence of substitutions distal to the phosphate group (position C-3, similar to compounds 1b-e, Scheme 1) [5][6][7]. Some of these compounds turned out to be crucial in mechanistic studies of PEP-utilizing enzymes, for instance in the establishment of the stereochemical course of enzymatic processes mediated by enzyme I of the PTS [8], UDP-GlcNAc enolpyruvyl transferase and 5-enolpyruvyl-shikimate-3-phosphate synthase [9], 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase [10], pyruvate kinase [11], KDOP synthase [12], enolase [13], PEP carboxykinase [14], and PEP carboxylase [15]. A representative example is the study of UDP-GlcNAc enolpyruvyl transferase, and 5-enolpyruvyl-shikimate-3-phosphate synthase, with (Z)-F-PEP (1b), an analogue that allowed the isolation and characterization of stable fluoro analogues of the otherwise unstable tetrahedral intermediate of the normal reaction [1].…”
mentioning
confidence: 99%